Program Bantu RCstructureMDL berbasis GNU Octave untuk Permodelan Otomatis Struktur Beton Bertulang pada OpenSees - Zacharias, Hendry David (CV. Gio Architect, 2026)
Structural analysis requires modeling using computer programs, one of which is OpenSees which uses TCL the one-line commands for modeling, analysis, material properties and other aspects. The lack of a GUI that makes users friendly in OpenSees can cause modeling errors. In this research, the Octave-based RCstructureMDL program was developed for automatic modeling of reinforced concrete structures on OpenSees. Three models with variations in the number of floors and frames in the X and Y directions are used to test the flexibility and the correctness of the model. Flexibility can be seen from the ease of creating modeling commands from three models by changing the variables nX, nY, nf, span_X, span_Y, and storey_Z. Support reaction value shows the same value as the vertical and horizontal load entered at all top floor points, so the model generated automatically using this program can be used for analysis.